Kitābah Online Learning Strategy With The Scamper Method - salimatul Fuadah; Muhammad Jafar Shodiq (Izdihar : Journal of Arabic Language Teaching, Linguistics, and Literature, 2022)
This research aimed to examine projects in creative Arabic writing by online learning with the scamper method. The object of research in this study was UIN Sunan Kalijaga's 4th semester of Arabic language and literature students. The research design used was True - Experimental Designs. Data collection techniques were observation, interviews, questionnaires, tests, and documentation. Research showed that the process of learning creative Arabic writing using online-based Scamper methods in kitābah courses is declared effective, with the results of the pretest test -t independent simple test showed that sig. 0.003 < 0.05. While the results of the posttest test-t independent simple test showed sig. 0.00 < 0.05. Strengthened by the analysis of the test-paired sample test showed a level sig. 0.00 < 0.05 so that it was concluded under Ha accepted and there was a significant difference. As for the results of learning to write creative Arabic with the scamper method after treatment in the experimental group, this can be seen from the increase in the experimental group by 18% and the control group only by 9,2% . This proved that there were significant differences before and after using learning strategies with scamper methods based on online experiment classes in writing creative Arabic on kitābah courses.